2006
DOI: 10.2139/ssrn.1448373
|View full text |Cite
|
Sign up to set email alerts
|

Rebuilding after Katrina: A Population-Based Study of Labor and Human Rights in New Orleans

Abstract: inteRnAtiOnAl HuMAn RigHtS lAW CliniC bOAlt HAll SCHOOl Of lAW uniVeRSitY Of CAlifORniA, beRKeleY the international Human Rights law Clinic (iHRlC) designs and implements innovative human rights projects to advance the struggle for justice on behalf of individuals and marginalized communities through advocacy, research, and policy development. the iHRlC employs an interdisciplinary model that leverages the intellectual capital of the university to provide innovative solutions to emerging human rights issues. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 11 publications
1
24
1
Order By: Relevance
“…Workers interviewed for this research confirmed the paucity of training and protective equipment documented elsewhere (Fletcher et al, 2006). They further elaborated on the condition of the equipment provided, casting doubt on its effectiveness and indicating that conditions may have been even worse than documented in quantitative surveys.…”
Section: Workers' Health In Jeopardysupporting
confidence: 77%
See 1 more Smart Citation
“…Workers interviewed for this research confirmed the paucity of training and protective equipment documented elsewhere (Fletcher et al, 2006). They further elaborated on the condition of the equipment provided, casting doubt on its effectiveness and indicating that conditions may have been even worse than documented in quantitative surveys.…”
Section: Workers' Health In Jeopardysupporting
confidence: 77%
“…All workers were Spanish-speaking day laborers, that is, they were hired on a daily or project basis by contractors or home owners without immediate prospects for long-term employment. Although Aguilar did not ask workers about their legal status, given findings from other studies, it is likely that the majority lacked legal documents (Aguilar & Podolsky, 2006; Fletcher, Pham, Stover, & Vinck, 2006; National Clearinghouse for Worker Safety and Health Training, 2006; Valenzuela et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…20 A large number of construction workers are now in New Orleans as the rebuilding continues; it is estimated that nearly half of the reconstruction workforce in New Orleans is Latino, of whom 54 percent are undocumented. 21 The population of New Orleans will continue to grow as rebuilding and redevelopment continue, but the size and composition of the future New Orleans population is likely to be smaller and more diverse than it was pre-Katrina.…”
Section: Health Care In New Orleans Post-katrinamentioning
confidence: 99%
“…This changed substantially after Hurricane Katrina devastated metropolitan New Orleans in August of 2005 after which many LMM came to work in reconstruction, comprising nearly half of the construction work-force (Donato and Hakimzadeh, 2006; Fletcher et al, 2006; Fussell, 2009) and resulting in a 77% increase in Latinos to the area (Passell, 2006). Like other new receiving communities, post-disaster New Orleans had little infrastructure to support the cultural, legal and linguistic challenges that are often available in more traditional receiving communities.…”
Section: Introductionmentioning
confidence: 99%